2019
DOI: 10.1038/s42003-019-0476-5
|View full text |Cite
|
Sign up to set email alerts
|

Paternal exposure to benzo(a)pyrene induces genome-wide mutations in mouse offspring

Abstract: Understanding the effects of environmental exposures on germline mutation rates has been a decades-long pursuit in genetics. We used next-generation sequencing and comparative genomic hybridization arrays to investigate genome-wide mutations in the offspring of male mice exposed to benzo(a)pyrene (BaP), a common environmental pollutant. We demonstrate that offspring developing from sperm exposed during the mitotic or post-mitotic phases of spermatogenesis have significantly more de novo single nucleotide varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Germ cells mutations may occur as a result of errors in DNA replication during gametogenesis, inefficient repair of DNA damages or exposure to mutagens during lifetime [61]. Yet we still know little about the role of environmental agents in the etiology of heritable mutations because germ cell mutations are rare (10 −8 per nucleotide) and difficult to detect because of technological limitations [60]. Many rodent germ cell mutagens have been identified; however, there are no accepted human germ cell mutagens [62].…”
Section: Mutagen-induced Cnv In Germlinementioning
confidence: 99%
See 1 more Smart Citation
“…Germ cells mutations may occur as a result of errors in DNA replication during gametogenesis, inefficient repair of DNA damages or exposure to mutagens during lifetime [61]. Yet we still know little about the role of environmental agents in the etiology of heritable mutations because germ cell mutations are rare (10 −8 per nucleotide) and difficult to detect because of technological limitations [60]. Many rodent germ cell mutagens have been identified; however, there are no accepted human germ cell mutagens [62].…”
Section: Mutagen-induced Cnv In Germlinementioning
confidence: 99%
“…The consequences of paternal exposure to benzo(a)pyrene (BaP), a ubiquitous environmental pollutant, on the mouse germline was studied using NGS and aCGH [60]. Paternal exposure to BaP induces single-nucleotide variants, indels and CNV in the offspring.…”
Section: Mutagen-induced Cnv In Germlinementioning
confidence: 99%
“…An additional human study byLaubenthal et al (2012) found that paternal preconception smoking was positively associated with single-and double-strand DNA breaks in the cord blood of their offspring. These human findings are complemented by a recent mouse study byBeal et al (2019) showing that paternal exposure to B[a]P significantly increased copy number duplications and de novo mutations in the offspring. Thus, there is growing evidence that paternal tobacco smoking and exposure to the components of tobacco smoke lead to an increase in the number of mutations that offspring inherit.…”
mentioning
confidence: 72%
“…These human findings are complemented by a recent mouse study by Beal et al . (2019) showing that paternal exposure to B[ a ]P significantly increased copy number duplications and de novo mutations in the offspring. Thus, there is growing evidence that paternal tobacco smoking and exposure to the components of tobacco smoke lead to an increase in the number of mutations that offspring inherit.…”
Section: Evidence Presented At the Workhopmentioning
confidence: 99%
“…Their elevated frequency among the offspring of irradiated males can be attributed to the delayed or compromised repair of radiation-induced clustered damaged sites [43]. The results of a recent study also show significant genome-wide changes in the spectrum of mutations in the germline of male mice exposed to chemical mutagen benzo(a)pyrene [44].…”
Section: Mutation Induction and Transgenerational Effectsmentioning
confidence: 99%